Vector Auto Regressive (VAR) Model untuk Analisis Hubungan Pembiayaan Murabahah dan Profitabilitas Bank Umum Syariah di Indonesia - Nurwan Nurwan (Program Pascasarjana STIE Amkop Makassar, 2022)
The increase in profitability is wrongly influenced by the volume of financing. One of the most frequently used financing in Islamic banks is murabahah financing. The purpose of this study is to see the relationship and reciprocal relationship between Murabahah and ROA at Islamic Commercial Banks. The data is obtained from the statistical reports of Islamic Commercial Banks in Indonesia from 2018 to 2020 published on the website https://www.ojk.go.id/id/kanal/syariah/data. The Vector Auto Regressive (VAR) model goes through several stages, namely: stationarity test using the unit root test (unit root test) with the Augmented Dickey Fuller Test (ADF Test) method, Cointegration Test, VAR model analysis and Impulse Response Function formation analysis. The results of the impulse response show that if there is a change in murabahah, the ROA will respond positively. This positive response indicates that the increase in murabahah will respond to ROA. This positive response is because the greater the murabahah financing that is distributed to the public, the bank will get a return on the financing provided to customers.